Strategi Pembinaan Pemimpin Berkarakter Kristen Sebagai Upaya Gereja Mempersiapkan Generasi Muda Menghadapi Bonus Demografi 2030 - Meriko Zonnedy Simangunsong; Yanto Paulus Hermanto (Sekolah Tinggi Teologi Simpson Ungaran, 2023)
2030 is fast approaching, and Indonesia will experience a demographic bonus. The Church and the State can work together to prepare the youth generation to be leaders in the future. This research aims to prepare the youth generation as leaders with Christian character and resilience in the face of Indonesia's demographic bonus in 2030 and how strategies for coaching. This research was conducted using a qualitative research method or literature study. The result of this research is that the church prepares the younger generation as leaders; the strategies that can be used to develop leaders with Christian character include firstly, disciplining leaders, secondly assisting (mentoring), thirdly practising serving a small flock, fourthly experiencing the baptism of the Holy Spirit, fifthly equipping leaders with counselling skills and sixth involving leaders in solving problems in the surrounding environment.